Representasi Perempuan pada Pemilihan Kepala Daerah: Ikhtisar Pilkada Serentak di Jawa Tengah 2020 - Marwah, Sofa; Catur Pratiwi, Oktafiani (Magister Ilmu Politik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2022)
This paper aims to examine the women's representation in Pilkada (local election) 2020 in Central Java. Studies on women's representation include descriptive representation, the backgrounds of the elected female regents, and gender issues in the campaign. The Pilkada 2020 has become more specific. Pilkada 2020 held during the covid-19 pandemic. The results show that the number of candidates participating in Pilkada 2020 in Central Java was decreasing. However, there is an increase in female regents elected in the Pilkada 2020, compared to the Pilkada 2015, as can be seen from both the number of female regent candidates and the number of elected female regents. Some of the women regents' backgrounds are incumbents and party cadres. Some of them also have husbands/fathers who have been prominent figures in the election area. Most of the elected female regents have included gender issues in campaign materials. Yet, gender perspective has not been strongly asserted in their proposed policies. Despite advancing slowly, the progress in political arena remains to bring optimism in gender equality promotion.